Sick Sinus Syndrome and Takotsubo Cardiomyopathy - Ahmed S. Yassin; Ahmed Subahi; Hossam Abubakar; Ahmed Rashed; Mohamed Shokr (Case Reports in Cardiology)
Background. Takotsubo cardiomyopathy is associated with increased risk of ventricular arrhythmias, atrial fibrillation, and bradyarrhythmias. However, sinus node dysfunction is relatively infrequent in the setting of takotsubo cardiomyopathy. Case Report. We are reporting a case of a 73-year-old woman with a history of asymptomatic sinus bradycardia who developed sick sinus syndrome complicated by takotsubo cardiomyopathy. Conclusion. Acute symptomatic sick sinus syndrome in patients with preexisting silent sinus node dysfunction can trigger takotsubo cardiomyopathy. Understanding precipitating factors of takotsubo cardiomyopathy and identifying the patients at risk of life-threatening arrhythmia can help in refining risk stratification and therapy planning. Patients with sick sinus syndrome complicated by takotsubo cardiomyopathy may benefit from pacemaker implantation. However, evaluation on a case-by-case basis is mandatory.